De-i-fuzzification of linear interval-valued intuitionistic fuzzy number and its application in operation research arena. (8th June 2023) - Chakraborty, Avishek; Pal, Shilpi; Mondal, Sankar Prasad; Alam, Shariful
In this article, we have envisaged the linear interval valued intuitionistic fuzzy number (IVIFN) from various viewpoints. We have introduced the technique of ranking by using the concept of distance measure of linear interval valued intuitionistic fuzzy number. Additionally, the concept of de-i-fuzzification is introduced here using two disjunctive logical approaches and its result is explained in this article which will help us converting a linear interval valued intuitionistic fuzzy number into a crisp number. Lastly, the validation of the model is observed by using two different real life problems firstly, in inventory control and secondly, in transportation arena. The paper suggests two different methods of de-intuitification in linear interval valued intuitionistic fuzzy domain and the comparison between the two methods by using a suitable algorithm has been observed in above real life scenarios that connects all invented results.